(untitled) (Bangladesh Journal of Child Health, 2010)
A cross-sectional community based study was conducted in four tea gardens of Sylhet division to assess the nutritional status of 1 to 5 years children of tea workers. Nutritional status was determined anthropometrically along with their socioeconomic background and the nutritional status was compared with the data obtained from national survey. Prevalence of wasting was 42.3% whereas that of stunting and underweight was 80.2% and 73% respectively. All these parameters are significantly higher than those obtained from national data (BDHS, 07). Though the children are breast fed at much higher rate in comparison with Bengali children, their mother’s educational status and body mass index are lower than that of Bengali population. The nutritional status of children of tea workers are worse than that of national level. Key words: Tea workers; nutritional status. DOI: 10.3329/bjch.v34i1.5696 Bangladesh Journal of Child Health 2010; Vol.34(1): 11-16